2018
DOI: 10.1039/c8tb01160e
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte-based physical adhesive hydrogels with excellent mechanical properties for biomedical applications

Abstract: Cytocompatible and adhesive polyelectrolyte-based physical hydrogels with reinforced mechanical strength for small molecule delivery and detecting doses of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…This kind of physical adsorption‐based adhesion may also be applicable for various dry surfaces (e.g., metals, ceramics, and plastics) and wet surfaces (e.g., hydrogels and biotissues); however, future extensive studies should be carried out to further clarify this. The adhesive property of our system is comparable to commonly used mussel‐inspired catechol‐based hydrogels and other recently developed adhesive hydrogels that rely on supramolecular interactions for adhesion (Table S1, Supporting Information) . Notably, while most adhesive hydrogels (apart from nanoparticle adhesives) require internal modification of the chemical structure—which ultimately changes the properties compared to the original unmodified hydrogel—our strategy only alters the surface structure.…”
mentioning
confidence: 62%
“…This kind of physical adsorption‐based adhesion may also be applicable for various dry surfaces (e.g., metals, ceramics, and plastics) and wet surfaces (e.g., hydrogels and biotissues); however, future extensive studies should be carried out to further clarify this. The adhesive property of our system is comparable to commonly used mussel‐inspired catechol‐based hydrogels and other recently developed adhesive hydrogels that rely on supramolecular interactions for adhesion (Table S1, Supporting Information) . Notably, while most adhesive hydrogels (apart from nanoparticle adhesives) require internal modification of the chemical structure—which ultimately changes the properties compared to the original unmodified hydrogel—our strategy only alters the surface structure.…”
mentioning
confidence: 62%
“…Recently, nanocomposite33 and supramolecular34 biocompatible hydrogels that are tough and self-healing have been synthesized using free-radical polymerization accompanying host–guest interaction,34 hydrogen bonding,33,34 electrostatic interaction33 and physical entanglement 33. Physical hydrogels with such properties have also been prepared from oppositely charged polyelectrolytes 30,3537. These polyelectrolyte complex gels utilize reversible ionic bonds for physical crosslinking and are potentially attractive biomaterials for in vivo applications because covalent crosslinking is not required.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liang et al reported a similar observation, where they have explained a comparative interaction between the polydimethyldiallylammonium chloride and poly(acrylic acid) in a poly(acrylamide) based hydrogel. 61 Morrow et al studied the elongation behavior of the extensor digitorum longus (EDL) muscle (a type of skeletal muscle) of a New Zealand white rabbit and found that it showed an ultimate tensile stress of 163 AE 75.7 kPa in the longitudinal direction. 62 In the case of our study, both the uncut hydrogel and self-healed hydrogel show a similar tensile behavior.…”
Section: Self-healing Study Of the Hydrogelmentioning
confidence: 99%